Hydroxysafflor Yellow A Exerts Anti-Inflammatory Effects Mediated by SIRT1 in Lipopolysaccharide-Induced Microglia Activation - Qin, Xiude; Chen, Juanjuan; Zhang, Guowei; Li, Chuanpeng; Zhu, Jinqiang; Xue, Hong; Li, Jinfang; Guan, Tianxiang; Zheng, Haotao; Liu, Yu; Cai, Haobin (Frontiers in Pharmacology, 2020)
Abnormal microglia activation causes sever neuroinflammation, contributing to the development of many diseases, yet the mechanism remains incompletely unknown. In current study, we identified that Hydroxysafflor yellow A (HYA), a chalcone glycoside derived from Carthamus tinctorius L effectively attenuates LPS-induced inflammation response in primary microglia via regulating the expression of inflammatory genes and remodeling the polarization of microglia. We also reported the effects of HYA on improving lipopolysaccharide (LPS)-stimulated mitochondrial dysfunction and oxidative stress for the first time. Interestingly, we found that HYA could serves as an effective SIRT1 activator. Deficiency of SIRT1 abrogates the protective effects of HYA against LPS-induced response. Overall, our data suggest HYA, a novel SIRT1 activator, could serve as an effective approach to treat LPS-induced neurodegenerative diseases.